CIVIL LAW ASPECTS IN THE MAKING OF A POWER OF ATTORNEY TO SELL IN THE PROCESS OF TRANSFERRING LAND RIGHTS - Kristanto, Yosua Yonathan; Khairunnisah; Pasaribu, Benhard Kurniawan (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
In order to overcome these obstacles, it is necessary to help other individuals resolve them, which then gave rise to the concept of representation, where a person acts on behalf of other individuals when resolving their interests. This is known as power of attorney, which is regulated in Article 1792 of the Civil Code. Power of attorney itself is an agreement that requires authority in taking action. This research relied on a variety of library sources, i.e. references that contain the latest scientific information or updated understanding of known facts or developing ideas. These sources include books, journals, dissertations, theses and other legal documents. The research findings show that abuse of power of attorney, especially when the action taken is not in accordance with the power of attorney granted, can have various legal consequences. Actions that exceed the limits of the power of attorney risk being null and void or at least not binding on the authorizing party, in accordance with the provisions of Article 1804 of the Civil Code which states that actions outside the power of attorney do not create rights and obligations for the authorizer. The liability of the proxy itself relates to two important aspects: freedom of contract and statutory provisions. Although they have different meanings, there are exceptions to the freedom of contract principle that allow the making of agreements as long as they are not contrary to applicable law.